(E)-Anethole microspheres as an alternative insecticide in funnel traps. (September 2021) - Pascual-Villalobos, M.J.; Castañé, C.; Martín, F.; López, M.D.; Guirao, P.; Riudavets, J.
Abstract: Pyrethroids are the insecticides most commonly used inside traps, and the lack of alternatives poses the risk of pests developing resistance. In this paper we present two (E)- anethole formulations (spray drying (SD) and oil emulsion entrapment (OEE) processes) that provide a controlled release of their bioactive ingredient in the vapour phase with insecticidal potential in funnel traps. An experiment with the two pyralid moths Ephestia kuehniella Zeller and Plodia interpunctella Hübner was set up at two pilot stores in Spain for a four-month period. The microspheres (4 g of SD powder/trap or 6 g of OEE beads/trap) remained effective for 100 days, killing the moths by volatile activity. The efficacy values were within the interval of 70–100% for the first half of the experiment, with a decrease afterwards. The OEE beads performed better than did SD powder in the long run: over 80% efficacy for the whole experiment. The OEE process gives more loading capacity (19.7 g of (E)- anethole per 100 g of beads) and entrapment efficiency (28.6 g of (E)- anethole encapsulated per 100 g of (E)- anethole added) and is slower in releasing the product. In a laboratory study for E. kuehniella, the LC50 was 58.2 mg/L for SD after 24 h exposure to vapours and 111.6 mg/L for OEE after 48 h exposure to vapours. Therefore, the SD powder provides a quicker release of the bioactive ingredient. The results indicate that encapsulated (E)- anethole could be a promising insecticide for mass trapping, mating disruption and attract and kill strategies. Graphical abstract: Image 1 Highlights: Controlled release formulations of (E)-anethole are insecticidal inside traps. Oil emulsion entrapment is an effective method of (E)-anethole encapsulation. MIcrospheres of (E)-anethole remain effective for more than four months against stored product moths.